2021
DOI: 10.21203/rs.3.rs-246918/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Study of the Predictors of Breastfeeding Self-Efficacy in Mothers During the Covid-19 Pandemic

Abstract: Background and Purpose: Breastfeeding has a vital role in ensuring the health of mother and infant, and ultimately the health of society. Breastfeeding self-efficacy is a strong predictor of the duration of breastfeeding, which in a variety of situations - including crises - may be affected by a number of factors. The aim of this study is to determine the predictors of breastfeeding self-efficacy in breastfeeding mothers during the Covid-19 pandemic.Materials and Methods: A cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…A study conducted in Brazil showed no significant association except with maternal age (15) (Dodt et al, 2012). The mean score for breastfeeding self-efficacy among the mothers in our study was 46.53±8.495 out of total score of 70 while a study conducted in Iran showed a mean score of breastfeeding self-efficacy among mothers was 58.19±10.48 out of 70 (16).…”
Section: Discussioncontrasting
confidence: 79%
“…A study conducted in Brazil showed no significant association except with maternal age (15) (Dodt et al, 2012). The mean score for breastfeeding self-efficacy among the mothers in our study was 46.53±8.495 out of total score of 70 while a study conducted in Iran showed a mean score of breastfeeding self-efficacy among mothers was 58.19±10.48 out of 70 (16).…”
Section: Discussioncontrasting
confidence: 79%
“…This result is consistent with previous studies conducted before the pandemic which proved that anxiety, social support, and bonding affected self-efficacy. 1 , 7 , 8 , 9 , 10 It is suggested to raise self-efficacy education, provide information and awareness and also psychological intervention for mothers. 1 The current study set the bonding variable as an intervening variable.…”
Section: Discussionmentioning
confidence: 99%